Die Europäische Bürgerinitiative – Eine Bestandsaufnahme - Lipphardt, Anne-Marie; et al. (Gesellschaft, Wirtschaft, Politik, 2014)

EHLSSA: Europe-Wide Online Learning For Seniors - Lipphardt, Anne-Marie (International Conference on the Elderly and New Technologies, 2015)

EHLSSA: Europe-Wide Online Learning For Seniors - Lipphardt, Anne-Marie; Slyschak, Anna (Revista Ariadna; cultura, educación y tecnología, 2016)
Technology dominates the future and it is increasingly penetrating culture and society. In the course of this trend, online learning is gaining importance and becoming a crucial and integral component of lifelong learning. Still, the group of senior citizens is one of the groups that are predominantly excluded from using new technologies, though digital devices provide each citizen with new opportunities and perspectives. The EHLSSA project– European Home Learning Service for Seniors Association – takes this finding as its starting point and develops e-learning solutions for seniors around Europe. The importance and added-value of specially adapted e-learning models for this highly heterogeneous group is presented in this articl
Keywords: senior learners; e-learning; pedagogy and didactics.

E-inclusion for seniors - online learning programs for older adults - Lipphardt, Anne-Marie; Esteller-Curto, R.; Fowley, Cathy; Papitto, Patrizia; Issakainen, Cecil (5th International conference on the elderly and new technologies, 2017)
This paper sums up the evaluation results of an e-learning ICT course for older adults inexperienced in using ICT and discusses possibilities and limits of online learning in general. As part of the European project EHLSSA (European Home Learning Service for Seniors Association), online course modules were developed to teach older adults basics in computer usage and in going online. In the first run 40 participants (age range 60-86 y.) from Germany and Spain participated in the online course. After the course run, feedback could be gathered in the form of a questionnaire with both open and close questions. The evaluation focused on satisfaction with the learning progress, course content and support during the course run. Additionally, questions on the appropriateness of e-learning for teaching this kind of content were posed to the participants. The results show that e-learning is a highly suitable learning method for older adults. Particularly the possibility to arrange learning time flexibly and to repeat content as often as necessary was positively highlighted by the participants. Even the preparation of content for ICT-beginners and applicability in the everyday life was assessed as successful. Social contact with other participants was not rated particularly high, but was at the same time not considered to be relevant for this kind of courses. In general, many respondents indicated that they wish that the offer of online courses for older adults will be extended and that they would like to participate in online courses in the future again. <
Keywords: e-learning; older adults; ICT course

ICT enhanced learning for older adults: Influencing factors on satisfaction and the role of learning motivation - Lipphardt, Anne-Marie; Held, Paul; Leen-Thomele, Eline; Hain, Lukas (Gerontechnology, 2018)
PURPOSE. Since Lifelong Learning has become a guiding principle of educational policy in many countries across the globe, several concepts in the field of educational gerontology were developed and implemented. In this context, also learning opportunities through ICT were tested and studies have proven a high suitability of e-learning for older people and their potentials for digital inclusion (1, 2, 3). Yet, little research has been done about the influence of learning motivation, personality traits and demographical aspects on e-learning success. METHOD. This paper discusses the results of the implementation and evaluation of four e-learning programs on ICT, culture, mentoring and well-being for older adults with 128 people (94 females, 34 males; mean age 67,12 years, SD 10,485) from five European countries. As part of the evaluation, satisfaction with course preparation and support, information on learning motivation, and aspects of e-learning as method were queried and analyzed with focus on differences with regards to gender, age, nationality, educational level, experience with ICT, life satisfaction, and health status. Learning motivation was further divided into motives of belonging, personal growth, instrumentality, and competition (4). RESULTS AND DISCUSSION. Findings show that older adults across all distinguishing criteria cope very well with diverse aspects of e-learning and highly benefit from the given advantages. No significant differences were found when comparing the subgroups. These results confirm study findings done at national level on suitability of e-learning (5). Differences could be found in learning motivation with regards to age, nationality, health status, gender. Younger participants take part more often for motives of competition, instrumentality and social belonging and older participants for motives of personal growth. Cross-country comparisons show significant differences with regards to diverse aspects in learning motivation. While personal growth was most important for German and Spanish participants, for participants from Finland motives of competition meant the most. As regards gender, men were more likely to take part for reasons of social belonging and instrumentality than women. Overall, results trigger considerations to develop e-learning programs adaptable to certain sub-groups (e.g. country-specific elements). <
Keywords: ICT; educational gerontology; e-learning: learning motivation

INNOVATIONS ON THE ADULTS AND SENIORS EDUCATION - Lipphardt, Anne-Marie (Inaugural Age Friendly Universities Conference 2015, 2015)
People age and the number of people aged 55 and above is growing steadily. At the same time old people do not want to be left behind but keep pace with the younger generation. The ever-increasing size of the digital world closely connected with the desire of seniors to engage in learning activities leads to infinite opportunities for further education. To meet the specific requirements of senior learners, innovative learning concepts are needed. The Innovation in Learning Institute (ILI) focuses on innovation processes in learning, training, and skills development. Developing innovative offers for older people is one of the main fields of work. ILI believes that e-learning is a very suitable instrument to deal with the heterogeneity of adult learners and to meet the learners’ needs and pace. In several projects, senior citizens are offered new education opportunities and are thus supported in becoming competent, independent ICT-users. The paper presentation will grant an insight into three successful projects of ILI conducted with and for seniors in the field of technology enhanced learning: · SenApp is a European project developing a training app for seniors · The project Lernkanal supports seniors in making video-clips on how to use new media, e.g. tablets · Within EHLSSA a digital learning infrastructure is developed and three e-learning courses are offered <
Keywords: e-learning; older learners; learning in later life

NETWORK OF STAFF AND TEACHERS IN CHILDCARE SERVICES - Lipphardt, Anne-Marie; Hahner-Korinski, Renate; Blatnik, Stanko; Selimović, Sanja; Szalma, Eva; Arenas Romero, M. Begona; Pokorny, Svenja (Journal of Educational and Instructional Studies in the World, 2015)
In this paper we present the results of the project“Network of Staff and Teachers in Childcare Services”, which is being realized within the framework of the EU Lifelong Learning Programme. The state of the art in staff development in Early Childhood Education and Care is related to the fragmented situation of systems and provisions across the EU: a common vision for childcare services is currently lacking in Europe, just as levels of investment differ greatly between Member States. Also, the picture in relation to childcare workforce varies significantly. Given the varied backgrounds of the EU Member States, there are no common recommendations/curricula, and practitioners as well as institutions at the national/regional level have little possibilities of sharing them. For this reason, the project has established a network in ECEC staff development: it contributes to overcome local visions, by creating links between institutions/practitioners/professionals, and by collecting learning resources in ECEC and making them available to a larger audienc
Keywords: Early childhood education and care; learning resources; network; childcare workforce

NEW CONCEPT FOR DIGITAL INCLUSION—ONLINE AND MOBILE LEARNING PROGRAMS FOR OLDER PERSONS - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Coroian, Anamaria Elena; Held, Paul (Innovation in Aging, 2017)
This paper sums up the evaluation results of two e-learning ICT courses for older adults: a tablet computer course and a regular computer course, and discusses the advantages of mobile learning and e-learning for older adults. As part of an European research project, the SenApp project, online course modules were developed, to teach older adults the first steps on a tablet computer, and evaluated (N=37, age range 58–93). The other course we analyzed, was an online learning course with regular computers and part of the LernHaus project in Germany (N=29, age range 50–89). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that all courses were rated good, compliance was very good and that support was a key factor for course success. Mobile learning was slightly easier for new learner

Older Adults and Learning Technology: Innovations in Adults‘ and Seniors‘ Education - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Held, Paul; Coroian, Anamaria Elena (Innovation in Aging, 2017)
This paper discusses the results of an empirical survey with 187 peopleabove the age of 50 years (mean age 68,4 yrs) on their digital behaviors, motivation as well as interests, and barriersagainst the use of new technologies and presents innovative learning approaches for older adults. The interviewswere conducted in five European countries (Finland, France, Germany, Ireland, Spain) as part of the research projectEHLSSA. The findings show that more than half of older adults are computer users and have Internet access at home.Reasons why they deal with digital technologies are mainly because they want to participate in the information societyand keep pace with the younger generation. Main obstacles are physical challenges, fears and reservations totechnology and the Internet, insecurity on how to work with digital devices and with regards to possibilities for supportin case something goes wrong or questions arise. According to the interviewees, successful learning concepts focuson experimental and active learning, including a more diverse media use, a series of real life examples, and theconnection with the daily life of older adults. Responses of ICT-beginners and experienced ICT-users were analyzedseparately and compared. The results have been used as the basis for the adaptation of learning approaches for thirdlevel education and the development of online course modules in the field of digital literacy and humanities-relatedtopics. The implementation of these courses started in May 2016 and will be completed in June 2017 with at least 800 participant

Senior Citizens Learning On-Line; Needs And Expectations - Escuder-Mollon, Pillar; Lipphardt, Anne-Marie (INTED2017 Proceedings, 2017)
Educational institutions are increasingly offering virtual learning spaces to students to acquire competences and skills regardless of time and space. The most common configuration is the blended learning (virtual and physical teaching mixed) but it is being increasingly offered completely virtual teaching, mainly to adults in very specific subjects in specialization course, or other job-skills subjects. This kind of learning is not advised in children, neither in senior citizens as some of the competences they have to reach require a face-to-face contact and real group interaction or when social contact is one of the priorities. Even we are aware of the limitations of full virtual learning, it is necessary to acknowledge the enormous advantages it provides, increasing the access of people to education (mostly if those life in rural areas, or disabled). Furthermore, it is also worth mentioning that nowadays, because of the great extend of technology in everyday life, the virtual socialization deserves as much attention as the real life socialization. Senior students are enrolled in educational institutions mainly because of personal motivations (not because of job skills or competitiveness) and they attend to courses because they want to keep active and up-to-date, sharing the time with other classmates, enjoying and learning from this experience. This interaction is reached thanks to physical learning environments, for this reason it is not usual to offer full virtual learning spaces for senior learners. Furthermore statistically senior citizens are not so computer skilled as younger, therefore, they prefer face-to-face learning. In the EHHLSA project we analysed the expectations and interests of the senior citizens about virtual learning, and the preferred topics. We also wanted to know their preferred method for learning and if they had experience on ICT mediated education, we wanted to know their experience. From previous results and data analysis it is possible to conclude that their involvement in on-line learning is a result of a decision originated mainly from their cultural context and social environment, that is the life-long learning attitude and the use of Internet because it is a social duty. Success on the first steps on on-line learning environments is based on course topics, the skills of the facilitator, the environment and an appropriate methodology. After this barrier is overtaken, there is an increase on the involvement on on-line learning platforms. This can be seen as a virtuous circle based on senior citizens experience and with a three dimensional aspects: learn and use of technology, learn new things and topics, and enjoy being part of the virtual community. The results of this research are framed in the “European home learning service for seniors association” (http://ehlssa.odl.org/) KA2 Erasmus + Strategic partnership projec

SENIOR STUDENTS IN VIRTUAL SPACES; THE TREASURE WITHIN - Lipphardt, Anne-Marie; Escuder-Mollon, Pillar; Adell, J.; Cabedo, S.; Esteller-Curto, R.; et al. (ICERI2015 Proceedings, 2015)
Virtual learning spaces are offered to students to acquire competences and skills regardless of time and space. Even the most usual configuration is the blended learning (virtual and physical teaching mixed), educational institutions also offer 100% virtual learning, mainly to adults in very specific subjects in specialization courses, or other job skills subjects. Even we are aware of the limitations of full virtual learning, it is necessary to acknowledge the enormous advantages it provides, increasing the access of people to education (mostly if those life in rural areas, or disabled). Furthermore, it is also worth mentioning that nowadays, because of the great extend of technology in everyday life, the virtual socialization deserves as much attention as the real life socialization. Senior students are enrolled in educational institutions mainly because of personal motivations (not because of job skills or competitiveness) and they attend to courses because they want to keep active and up-to-date, sharing the time with other classmates, enjoying and learning from this experience. This interaction is reached thanks to physical learning environments, for this reason it is not usual to offer full virtual learning spaces, furthermore when statistically senior citizens are not so ICT skilled as younger (Information and Communication Technologies, that is mainly computer and internet use). The Senior Citizens' University (SCU), started in the course 2011/2012 a pilot curse (using Moodle) with 30 students (senior learners over 55), after this experience, each year the number of subjects and students have been increasing reaching to 12% (that is 114 learners) of the total students from the SCU (in the course 2014/2015 954 students were enrolled in the SCU). Each of the subjects lasts for a semester (45 months) This papers aims to show the results of the use of virtual learning to senior citizens, the difficulties that have appeared and how we tried to solve them year after year. We consider that the virtual teaching is now consolidated with enough quality as a viable approach for senior citizens that do not have possibilities to attend real classes, or that want to use computer mediated learning (a e-inclusion characteristic) Specially remarkable has been noted in teaching-learning process; it has increased in complexity enormously, allowing senior learners to acquire competences difficult to reach in real classrooms; therefore we recommend its implementation by other educational institutions focused on seniors. We show in the paper how the senior learners acquired competences not only related to the content of the subject (that usually was related to history and society areas) but new ways of communication, collaboration, learning and sharing using the ICT. Their feedback (using qualitative research) and also the teachers’ experience has showed the impact the participation in this kind of education had in their technological attitudes and competences. This kind of teaching, when designed based on senior learners needs and requirements, implementing instructional, constructivism, and connectivism pedagogies, showed that made them to learn the course content, but also learn to share, learn to do and learn to learn in the information age society. The results of this research are framed in the “European home learning service for seniors association” (http://ehlssa.odl.org/) KA2 Erasmus + Strategic partnership projec
Keywords: senior; virtual learning; elderly; pedagogy; gerontology; blended learning; moodle